Renal Biomarker and Angiostatic Mediator? Cystatin C as a Negative Regulator of Vascular Endothelial Cell Homeostasis and Angiogenesis - Ralf A. Benndorf (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
See Article by Li et al.